2011
DOI: 10.1063/1.3554641
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulations of confined liquids: An alternative to the grand canonical Monte Carlo simulations

Abstract: Commonly, the confinement effects are studied from the grand canonical Monte Carlo (GCMC) simulations from the computation of the density of liquid in the confined phase. The GCMC modeling and chemical potential (μ) calculations are based on the insertion/deletion of the real and ghost particle, respectively. At high density, i.e., at high pressure or low temperature, the insertions fail from the Widom insertions while the performing methods as expanded method or perturbation approach are not efficient to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…In both methods ten rates of dehydroxylation were explored from 0% to 100%. Because it has been shown that the polarizability of Na + and water molecules does not impact the structure, dynamics, or dielectric properties of water [23,27], a nonpolarizable model was considered to model Na + [30] while the rigid nonpolarizable TIP4P/2005 model was used to model the water molecules [31,32]. The number of Na + ions corresponded to the number of removed hydrogen atoms of SiOH (236 initially).…”
Section: A Silica Nanotubementioning
confidence: 99%
See 3 more Smart Citations
“…In both methods ten rates of dehydroxylation were explored from 0% to 100%. Because it has been shown that the polarizability of Na + and water molecules does not impact the structure, dynamics, or dielectric properties of water [23,27], a nonpolarizable model was considered to model Na + [30] while the rigid nonpolarizable TIP4P/2005 model was used to model the water molecules [31,32]. The number of Na + ions corresponded to the number of removed hydrogen atoms of SiOH (236 initially).…”
Section: A Silica Nanotubementioning
confidence: 99%
“…Force field parameters of the silica nanopore are in Refs. [27,28]. Although the silica matrix was subsequently kept rigid, rotation around the Si-O bond of the hydroxyl groups was allowed from the application of a bending potential between Si-O-H. Motion of hydrogen atoms of SiOH was also performed from a stretching potential.…”
Section: A Silica Nanotubementioning
confidence: 99%
See 2 more Smart Citations
“…Let us note that the RDFs inside the CNT have higher intensity than in the bulk phase, which results from excluded volume effects. [ 55,72–75 ]…”
Section: Resultsmentioning
confidence: 99%